2016
DOI: 10.1183/13993003.01711-2015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NHANES III and ERS/GLI 12 for airway obstruction classification and severity

Abstract: The diagnosis and severity categorisation of obstructive lung disease is determined using reference values. The American Thoracic Society/European Respiratory Society in 2005 recommended the National Health and Nutrition Examination Survey (NHANES) III spirometry prediction equations for patients in USA aged 8-80 years. The Global Lung Initiative 2012 (GLI 12) provided spirometry prediction equations for patients aged 3-95 years. Comparison of the NHANES III and GLI 12 prediction equations for diagnosing and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
3
13
2
Order By: Relevance
“…Our results were similar to a previous finding suggesting that the rates of severity classification of AO (COPD and asthma) were changed when changing from the ECSC to the GLI2012 reference equations [13]. However, two other studies showed a concordance of severity classification between the NHANES III and the GLI2012 reference equations [10,16].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results were similar to a previous finding suggesting that the rates of severity classification of AO (COPD and asthma) were changed when changing from the ECSC to the GLI2012 reference equations [13]. However, two other studies showed a concordance of severity classification between the NHANES III and the GLI2012 reference equations [10,16].…”
Section: Discussionsupporting
confidence: 89%
“…Another study suggested that changing from the Stanojevic to the GLI2012 reference equations caused an increase of 32% in the rate of AO [10]. However, the other studies showed a concordance of the diagnosis associated with AO when changing between the NHANES III and GLI2012 [10,12,16,17] due to the higher LLN value of the FEV1/FVC ratio in the Siriraj reference equation when compared to the GLI 2012 reference equations. Thus, the differences in the rate of diagnosis associated with AO between the two references equations are likely to have occurred when the ratio of FEV1/FVC was close to the LLNs values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated potential risk factors as well as the relation of FVC to the health and socioeconomic status. Since the use of universal cut-offs to define abnormal spirometry is contentious [15], we have analysed FVC as a continuous variable to assess its associations, including those with age, sex and ethnicity. In addition, we also studied similar associations with pre-bronchodilator FVC; and pre and post-bronchodilator FEV1.…”
Section: Introductionmentioning
confidence: 99%
“…A previous US study proved that, in Caucasians, the difference between different reference equations in LLN of FEV1/FVC might be influenced by height and age. 18 Both of the two versions have the average age at which the LLN of FEV1/FVC fall below 0.70 is over 60 years, which is older than the results of a previous study (42 and 48 years in males and females). 19 This may be due to differences in the race of study populations.…”
Section: Discussionmentioning
confidence: 59%